Synthesis and Biological Evaluation of New Boron Compound with Cephalexin and some of Its Transition Metal Complexes - Asmaa Mohammed (Journal of Global Pharma Technology, 2018)
Synthesis of the ligand [ 7-(2-amino-2-phenylacetamido)-3-methyl-8-oxo-5-thia-1-azabicyclo[4.2.0]oct-2-ene-2-carboxylic boric anhydride] by the reaction of cephalexin monohydrate with boric acid in a mole ratio (1:1). The metal complexes of this ligand with Cr(III),Co(II),Ni(II)and Cu(II) have been also synthesized .The ligand and its metal complexes were characterized by UV-Vis, FTIR, 1HNMR, 13CNMR , atomic absorption spectra, CHNS analysis, melting point ,magnetic susceptibility and molar conductivity measurements . The antimicrobial activity for the ligand and its metal complexes were evaluated against Pseudomonas auroginosa (G-), Staphylococcus aurus (G+), Klebsiella pneumonis (G+) and Staohylococcus epidermidis (G+) and Asporgillus as fungi. Keywords: Boron compound, Cephalexin.